The role of nocturnal polysomnography in assessing children with Chiari type I malformation - Dhamija, Radhika; Wetjen, Nicholas M.; Slocumb, Nancy L.; Mandrekar, Jay; Kotagal, Suresh (Clinical neurology and neurosurgery, 2013)
To evaluate nocturnal polysomnogram findings in children with suspected symptomatic Chiari type I malformation, correlate them with clinical and magnetic resonance imaging data and to determine if this information has value in clinical decision making process. A retrospective review identified 24 children with type I Chiari malformation, presumed symptomatic who had undergone neurological assessment, cranial magnetic resonance imaging and nocturnal polysomnography. Perimedullary subarachnoid space effacement on the magnetic resonance studies and the magnitude of cerebellar tonsillar descent in relation to the McRae line were correlated with frequency of obstructive or central sleep apnea, number of cortical arousals and evidence of impaired vocal mobility on laryngoscopy. The Wilcoxon rank sum test was applied for continuous variables and the Fisher exact test for categorical variables. The median age of the subjects was 6 years. The findings from 16/24 subjects with perimedullary subarachnoid space effacement (effaced group) were compared with those of 8/24 in the non-effaced group. The central apnea index [1.5 (IQR 1–3.5) versus 0.5 (IQR 0–1.5)] and cortical arousal index [12 (IQR 10–19) versus 8 (IQR 6.5–9)] were significantly higher in the effaced group than in the non-effaced group (p=0.0376 and 0.0036 respectively). Greater descent of tonsils as measured by distance from the McRae line to the tonsil tip was associated with significantly higher central apnea index, total arousal index and respiratory event related arousals. Measurements of clivus-canal angle, Klauss index and pB-C2 line did not correlate with abnormalities on polysomnography. The central apnea and arousal indices derived from the nocturnal polysomnogram correlate well with magnetic resonance imaging findings of subarachnoid space effacement and degree of tonsillar herniation. In children with Chiari type I malformation, the nocturnal polysomnogram findings provides important information that aids in the decision making process about proceeding with surgical decompression.